Predictors of age at first child’s birth and contraceptive use among men in Uganda [version 1; peer review: 1 approved with reservations, 1 not approved] - Nsobya, Henry; Kabagenyi, Allen; Rusatira, Jean Christophe (Gates Open Research, 2019)
Globally, research on age at first child’s birth among men has been neglected especially in Africa. Consequently, little is known about its impact on male involvement in reproductive health. This paper examined the socio-demographic, economic and proximate predictors of age at first child’s birth among men aged 15- 54 years in Uganda. Methods: We used the 2016 Uganda Demographic and Health Survey (UDHS) on a sample of 3,206 men aged 15-54 years who had a biological child. The outcome variable was age at first childbirth categorized as: below 17, 18-24 and 25 years and above (25+). Analysis was done using descriptive statistics, un-adjusted and adjusted multinomial regressions with significance level at 95%. Results: Median age at first child’s birth was 22 years (IQR = 20-25). The majority of men (62.4%) had fatherhood onset between 18 and 24 years. Only 5.2% had fatherhood onset at 17 years or earlier, increasing to 32.4% at 25+. Respondents whose first sexual encounter was before 18 years was 44.3% and 92.7% by 24+. Few respondents (44.1%) reported use of any contraceptive methods. Anglican religion (RRR=1.62; CI 1.06 – 2.46) or not having attended school (RRR=2.20; CI 1.02-4.71) were predictors of childbirth onset before 17 years. Age of sex debut at 18 years or higher (RRR= 2.09, CI 1.72 – 2.54) and secondary and above education (RRR = 1.76, CI 1.42-2.18) were predictors of fatherhood onset at 25+. Contraceptive use among men had no association with age at first child’s birth. Conclusion: These findings are important for strategic allocation of resources to curb early onset of fatherhood among adolescent and young men under the age of 25 years. They highlight the need for gender-sensitive interventions targeting men for behavioral change, participation in Sexual and Reproductive Health Rights (SRHR) programming and improved access to services delivery.
Keywords: Teenage Fatherhood; First Child Birth; Male Involvement; Reproductive Health; Uganda